Studies of Herbal Medicine in Stroke: A Five-Year Bibliometric Documentation - Makkiyah, Feda Anisah (Journal of Data Science, Informetrics, and Citation Studies)
Indonesia remains a concerning location for the prevalence of stroke, which is considered high. The current treatment for stroke ischemia, rtPA, is costly, has side effects, and is only effective within 5 hr of onset. As a result, there is a growing interest in alternative therapies such as herbal medicine. This study examines the recent focus on herbal medicine in stroke research and aims to provide a framework for policy and strategic interventions to address this disease. We conducted a bibliometric analysis on herbal medicine in Stroke between 2017 and 2022. We retrieved published documents from Scopus by using keywords. We imported articles from Scopus, and we reported the trends. The visual analysis using VOS viewer version 1.6.18 to visualize publications on the keywords, countries, and author. China is the number one country whose authors wrote this issue. The number of articles about this issue reached a peak in 2021 and got down in mid-2022. Even though the prevalence of Stroke is high in Indonesia, none of the recent publications come from Indonesia. As the country with the most herbal medicine, Indonesia's authors should be more productive in writing about herbal medicine in Stroke.
Keywords: Bibliometric; Cerebrovascular attack; Phytomedicine; Trend.